Variance in caregiver burden predicted by patient behaviors versus neuropsychological profile. Issue 5 (3rd September 2018) - Branger, Camille; Enright, Joe; O'Connell, Megan E.; Morgan, Debra G.
ABSTRACT: Informal caregivers provide the majority of care to persons with dementia; efforts to support caregivers' well-being are increasingly important in the context of limited formal healthcare supports. Informal caregiving is commonly associated with caregiver burden and burden may depend upon patient characteristics including neuropsychological profile, dementia severity, and dementia etiology. This study investigated predictors of caregiver burden in a sample of 213 Memory Clinic patients diagnosed with dementia and whose caregivers provided collateral information. Caregiver burden was similar irrespective of dementia etiology. Beyond the expected predictive value of dementia severity on caregiver burden, patient behavioral symptoms, functional dependence, and caregiver psychological distress were predictive of caregiver burden. In contrast, care-recipient neuropsychological performance did not predict burden. These findings suggest that beyond severity of dementia, specific behavioral disturbances predict caregiver burden which may have implications for programming and intervention aimed at supporting and sustaining caregivers in their role.